Affective relations and personal bonds in hellenistic antiquity : studies in honor of Elizabeth D. Carney - D'Agostini, Monica; Anson, Edward M.; Pownall, Frances, 1963- (Oxbow Books, 2020)
The intense bonds among the king and his family, friends, lovers, and entourage are the most enticing and intriguing aspects of Alexander the Great's life. The affective ties of the protagonists of Alexander's Empire nurtured the interest of the ancient authors, as well as the audience, in the personal life of the most famous men and women of the time. These relations echoed through time in art and literature, to become paradigm of positive or negative, human behavior. 0By rejecting the perception of the Macedonian monarchy as a positivist king-army based system, and by looking for other political and social structures Elizabeth Carney has played a crucial role in prompting the current re-appraisal of the Macedonian monarchy. Her volumes on Women and Monarchy in Ancient Macedonia (University of Oklahoma Press, 2000), Olympias: Mother of Alexander the Great (Routledge, 2006), Arsinoe of Egypt and Macedon: A Royal Life. (Oxford University Press, 2013) have been game-changers in the field and has offered the academic world a completely new perspective on the network of relationships surrounding the exercise of power. By examining Macedonian and Hellenistic dynastic behavior and relations, she has shown the political yet tragic, heroic thus human side, thus connecting Hellenistic political and social history.